Use of patient image for medical marketing - Ivankovics, Ivan Gregório; Hurtado Madueno Júnior, Carlos Rafael; Deziderio, Aline Goulart; Costa, Débora Caroline Silva; Mesquita, Lázaro José Batista da Silva; Vieira, Gislaine dos Santos Rodrigues; Falqueti, Airton Batista; Nunes, Rui (Acta Bioethica, 2023)
The use of imagem strategies in medical socieal networks is increasingly widespread, meeting the ethical limit established by the CEM. Knowing this, the present study sought to understand the problem of patient exposure in medical social networks. For this, a literature review was carried out from the Scientific Electronic Library Online (Scielo), Pubmed, UpToDate, LILACS databases, articles in English, Spanish and Portuguese published from 2018 onwards were included. Thus, a tendency was noticed in some cities to create laws to regulate this exposure, given that the use of images has become routine in medical advertising, as a way to demonstrate results. However, this practice is greatly accompanied by ethical failures as recommended by the CFM.